2021
DOI: 10.1111/jfpp.15733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoemulsion loading a mixture of clove essential oil and carboxymethyl chitosan‐coated ε‐polylysine on the preservation of donkey meat during refrigerated storage

Abstract: The consumption of refrigerated meats has increased rapidly because of its better flavor, the improvement of meat quality, water-holding capacity, and nutrition (Zhao et al., 2019). Donkey meat contains high protein and polyunsaturated fatty acids, which makes it easy to decay and oxidative deterioration. Slaughtering, cutting, transportation, sales, and freezing may cause microbial contamination and oxidative deterioration, thereby reducing the shelf life of meat, in which the oxidative deterioration of meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Table 2 summarizes the L* value, b* value and a* value of chilled beef in different treatments. The improved meat brightness can be related to high myofibril degeneration [41]. The results show that the L* value was directly proportional to the extension of storage time.…”
Section: Analysis Of Chromaticity Of Chilled Beefmentioning
confidence: 83%
See 1 more Smart Citation
“…Table 2 summarizes the L* value, b* value and a* value of chilled beef in different treatments. The improved meat brightness can be related to high myofibril degeneration [41]. The results show that the L* value was directly proportional to the extension of storage time.…”
Section: Analysis Of Chromaticity Of Chilled Beefmentioning
confidence: 83%
“…Based on the method of Wei et al [41] with slightly modifications, meat samples were mixed with trichloroacetic acid solution and homogenized for 60 s, and then centrifuged at…”
Section: Determination Of Thiobarbituric Acid (Tbars) Valuementioning
confidence: 99%
“…Cinnamon-perilla EO-NE with collagen emulsifier can preserve fish fillets by increasing antioxidant activity [70]. Clove EO-NE with polylysine and carboxymethyl chitosan was able to stabilize pH, prevent microbial proliferation, reduce protein and fat oxidation, inhibit discoloration, maintain cohesiveness, maintain cohesiveness, and inhibit the decrease in elasticity in donkey meat [63].…”
Section: Current Use Of Nanoemulsion In Meat Productmentioning
confidence: 99%
“…Moreover, from a particle size viewpoint, NEs (98.2 to 258 nm) can minimize protein damage more effectively than macroemulsions (370 to 460 nm) Zixiang et al [63] and Khan et al [54] due to the high surface area for free radical binding and starting a chelating response against it. The thiobarbituric acid reactive substance (TBARS) in lamb meat is reduced significantly by NEs (chitosan and Satureja) [87].…”
Section: Functionality Improvement Of Meat Productmentioning
confidence: 99%
“…Nevertheless, the ease of the surface functionalization of chitosan could prompt its aqueous solubility and open up new avenues for enhancing the biological effects of NEs. To name a few, carboxymethyl chitosan plays an important synergistic role in the formulation of clove essential oil (CEO) nanoemulsion by enhancing its physical stability and promoting its antimicrobial potential for prolonged meat preservation applications [ 14 ]. Another study revealed that using amphiphilic chitosan for nanoencapsulation lemongrass essential oil (LEO) not only enhances the physical stability of the obtained LEO-based NEs but also increases their antimicrobial activity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%